Recent applications of residual stress measurement techniques for FSW joints: a review - Glaissa, Mustafa Ali A.; Mohammed Asmael,; Zeeshan, Qasim (Penerbit Universiti Kebangsaan Malaysia, 2020)
Quality control of welding processes plays a significant role in characterizing of the weld quality. Various Non-Destructive Method (NDM), Semi-Destructive Method (SDM) and Destructive Method (DM) are all employed for welding inspection and quality control. This paper presents a review of the recent research onthe quality control of Friction Stir Welding (FSW) processes of similar and dissimilar alloys. Based on previews articles, this paper focuses on comparing various inspection techniques with the effect of different FSW parameters such as; tilt angle (deg°), rotation speed (rpm), welding speed (mm/ min) and axial applied force (N)on the formation or residual stresses across welded joints. Additionally, the inspection measuring parameters, machine used, and material specification are also discussed. Recent studies are classified based on the measuring approach. The key findings for each inspection method are also presented. Researchers report that NDM, SMD and DM greatly contribute in detecting residual stresses of welded joints. However, some techniques like Deep-hole drilling technique have not been extensively applied for quality inspection of the FSW process. This paper reviews the various testing techniques for the FSW, aiming to let more experts know the current research status and also provide some guidance for future research.